Risiko dan pengurusannya dalam pembinaan : perspektif kontraktor - Abd. Kadir, Aslila (2006)
Risk is a condition that cannot be identified accurately. Its existence is always referred to a situation that can cause negative effect such as destruction or loss. In construction works, the existence of risk is always linked to project delay or cost increase. However, this negative effect can be avoided or minimised. As a party who is responsible in running the construction works, contractors should be prepared to manage construction risk as to ensure the success of the project. The aim of the project is to examine risk that is normally faced by contractors and how they manage the identified risk. The scope of the project focuses on the existence of risk during the construction progress. Hence, only experience contractors within Johor State are chosen. This project involves literature review and questionnaire distributed to contractors. Gathered data was analysed using SPSS method. The findings show that the contractors were fully aware of the existence of risk and believe that risk was something that needs to be identified and managed. Risk related to finance was type of risk that is commonly faced by the contractors and it contributed the highest level of seriousness in construction. As a mean to minimise the risk effect, the contractors felt comfortable to do and early work program. However, other risk management method were also implemented, such as to do analysis on previous project and appointed consultant